Australian Children with Special Health Care Needs: Social-Emotional and Learning Competencies in the Early Years - Whiteford, C; Walker, S; Berthelsen, D (My University, 2013)
This study examined the relationship between special health care needs and social-emotional and learning competence in the early years, reporting on two waves of data from the Kindergarten Cohort of Growing up in Australia: The Longitudinal Study of Australian Children (LSAC). Six hundred and fifty children were identified through the two-question Special Health Care Needs Screener as having special health care needs. Children with special health care needs were more likely to be male, to have been of low birth weight, to be taking prescription medications, to be diagnosed with a specific health condition and to be from families where the mother was less well educated. These children scored significantly lower on teacher-rated social-emotional and learning competencies prior to school compared to a control group of children without special health care needs. Multiple regression analyses indicated that being identified with a special health care need prior to school predicted lower social-emotional and learning competencies in the early years of school. Results are discussed in terms of the implications for policy and practice.
Keywords: Children -- Early childhood; Child Development -- Emotional; Health; Childhood and child development; Health and wellbeing; Child Development; Health; Children; Emotional; Early childhood; Health and wellbeing; Childhood and child development